Bio-assisted synthesized Ag(0) nanoparticles stabilized on hybrid of sepiolite and chitin: efficient catalytic system for xanthene synthesis - Kahangi, Fatemeh Ghoreyshi (Sci Rep, 2020)
In this work, with the use of two natural compounds, chitin and sepiolite clay, a novel covalent hybrid is fabricated and applied as a support for the stabilization of silver nanoparticles with the aid of Kombucha extract as a natural reducing agent. The resultant catalytic system, Ag@Sep-N–CH, was characterized via XRD, TEM, FTIR, ICP, SEM, TGA, UV–Vis and BET. It was found that fine Ag(0) nanoparticles with mean diameter of 6.1 ± 1.8 nm were formed on the support and the specific surface area of the catalyst was 130 m(2) g(−1). The study of the catalytic performance of Ag@Sep-N–CH for catalyzing synthesis of xanthenes in aqueous media under mild reaction condition confirmed that Ag@Sep-N–CH exhibited high catalytic activity and could promote the reaction of various substrates to furnish the corresponding products in high yields. Moreover, the contribution of both chitin and sepiolite to the catalysis has been affirmed. It was found that hybridization of these two components led to synergistic effects and consequently improved the observed catalytic activity. Notably, the catalyst was recyclable up to several reaction runs.